A Time-Based Two-Stage Model of Visual Selection: Evidence From Standard Visual Search Tasks. - Zheng, Yujie; Xin, Keyun; Li, Zhi (Journal of Experimental Psychology. Human Perception & Performance, 2026)
How does the visual system achieve efficient information selection under limited processing capacity is a fundamental question in cognitive psychology. Through three experiments, the present study reveals a time-constrained two-stage visual selection mechanism. Experiment 1's color search tasks demonstrated bilinear Search Time × Set Size functions, with a clear kink point at 50–100 ms after stimulus onset, showing shallower slopes (2.7–10.4 ms/item) before versus steeper slopes (10.7–20.7 ms/item) after, indicating two distinct processing stages. Experiment 2 extended these findings to digit search: despite capacity differences (color = 7.6 vs. digit = 3.8 items), the critical kink point time remained stable (60–70 ms), suggesting cross-stimulus generalizability. Experiment 3 disrupted this bilinear pattern by delaying search onset, confirming its time dependence. Individual analyses showed unimodal kink point time distributions (peak 60–80 ms) but multimodal set-size distributions, indicating time-driven stage transitions. These findings establish that visual selection has a time-based parallel-to-serial transition, and the early parallel stage has a stimulus-dependent capacity. This two-stage selection model integrates the core tenets of the Guided Search model and attentional window theories, offering a new perspective for the architecture of visual information processing. Public Significance Statement: Because of limited processing capacity in our visual system, we rely on attention to selectively process task-relevant information. Most traditional theories suggest that visual attention selection operates either in a serial (item-by-item) or parallel (cluster-based) manner, depending on stimulus characteristics. This study reveals that visual selection in fact functions through a time-based two-stage process: an initial parallel stage for simultaneous cluster processing, followed by a serial stage for item-by-item processing. The capacity of the parallel stage dynamically adjusts based on stimulus characteristics, functioning like a dynamically adjustable selection window. This newly discovered mechanism could bridge two major attention theories (the Guided Search models and attentional window theories), creating a unified framework that offers a more comprehensive account for attentional phenomena, particularly those showing temporal dynamics.